Understanding plant to extract ratios in botanical extracts - Monagas, Maria; Brendler, Thomas; Brinckmann, Josef; Dentali, Steven; Gafner, Stefan; Giancaspro, Gabriel; Johnson, Holly; Kababick, James; Ma, Cuiying; Oketch-Rabah, Hellen; Pais, Pilar; Sarma, Nandu; et al. (Frontiers in Pharmacology, 2022)
Dietary supplement current good manufacturing practice (cGMP) requires establishment of quality parameters for each component used in the manufacture of a dietary supplement to ensure that specifications for the identity, purity, strength, composition, and limits on contaminants are met.* Compliance with botanical extract ingredient specifications is assured by using scientifically valid methods of analysis, the results of which are reported on certificates of analysis (CoAs). However, CoAs routinely include additional data that are not amenable to verification through methods of analysis. Such descriptive information may include Plant to Extract ratios, which are ratios of the quantity of botanical article used in the manufacture of the extract to the quantity of extract obtained. Plant to Extract ratios can be misleading when their meaning is not clearly understood. Plant to Extract ratios do not completely describe botanical extracts because other important factors influence the make-up of final extracts, such as the quality of the raw starting material (as can defined by pharmacopeial standards), extraction solvent(s) used, duration and temperature of extraction, and percentage and type of excipients present. Other important qualitative descriptions may include constituent “fingerprinting.” Despite these issues, Plant to Extract ratios are often used as a measure of extract strength for dosage calculations. This article defines and clarifies the meaning of Plant to Extract ratios and their proper use in describing and labeling botanical extract ingredients and finished products containing them.